Cleaning of thick films using liquid jets. (March 2019) - Tuck, Jessica P; Alberini, Federico; Ward, Dick; Gore, Bill; Fryer, Peter J
Abstract: Cleaning of process plants is important to ensure product purity and safety. Cleaning is however expensive with respect to energy, waste and time. It is important to be able to minimise losses from cleaning, by maximising product recovery and reducing waste. Viscous food and personal care products can form thick layers on process surfaces. Cleaning of a surface by a water jet has been studied here. Two modes of cleaning are identified experimentally; for thin films, cleaning is by formation of a crater that expands with time, whilst for thick films a 'blister' forms in which water spreads underneath the deposit. The blister eventually cleans, but over a much longer timescale than for the thinner film. The cleaned area after 10 seconds is comparable in size to the blister area after less than half a second of cleaning. This behaviour has implications for the cleaning of real systems.